PENANGANAN KASUS BULLIYING DENGAN CARA EDUKASI EMOSIONAL - Yanti Kirana; Fikry Latukau; Tedy Subrata; Ria Trisnomurti (Collegium Studiosum Journal, 2026)
An agreement to purchase land creates rights and responsibilities for both Bullying is a negative act repeatedly committed by a group of people with the intent to cause harm. It is not limited to physical actions; bullying manifests in various forms, ranging from cyberbullying and sexual harassment to verbal abuse. If not properly addressed, these actions can have negative consequences for the victims. Bullying is an intentional act designed to harm others physically, verbally, or emotionally. This phenomenon resembles an iceberg; many victims are reluctant to report it, and some members of society still dismiss it as mere joking. Data from the Indonesian Child Protection Commission (KPAI) and the Indonesian Education Monitoring Network (JPPI) indicate a sharp rise in cases of violence against children in 2024—an increase of over 100% compared to 2023. Emotional education is a learning process that helps individuals recognize, understand, manage, and express their own emotions as well as those of others in a healthy manner. Its goal is to foster self-awareness, self-control, empathy, and social skills—enabling individuals to build healthy relationships, make responsible decisions, and achieve emotional well-being. Relevant legal frameworks include Law Number 23 of 2002 concerning Child Protection (subsequently amended by Law Number 35 of 2014 and Law Number 17 of 2016), Law Number 12 of 2022 concerning the Crime of Sexual Violence (TPKS), and the Criminal Code (KUHP) Chapter XXIII regarding Extortion and Threats (Article 368 paragraph 1). This study employs both normative-juridical and empirical-juridical approaches, utilizing literature reviews and secondary data analysis. The research focuses on addressing bullying cases through emotional education.